Final questions and comments presented by John M. Gottman, Julie Gottman, and Susan Johnson. - Gottman, John Mordechai; Gottman, Julie Schwartz; Johnson, Susan, 1948- (The video journal of counseling and therapy, 2014., 2013)
A presentation by John and Julie Gottman and Susan Johnson about working with couples dealing with stress followed by a wrap up discussion of the summit. The presentation includes footage of counseling sessions and role playing. This presentation was part of the Johnson-Gottman Summit.